UTILIZING PICTURE – BASED STAD COOPERATIVE LEARNING MODEL TO IMPROVE STUDENTS’ LEARNING OUTCOMES - Ainun Jariyah; Veronika P. Sinta Mbia Wae (JURNAL PAJAR (Pendidikan dan Pengajaran), 2021)
This study aimed to determine (1) the use of the picture-based STAD cooperative learning model for grade VIII students at SMP Negeri 2 Ende Selatan; (2) the students’ learning outcomes at grade VIII at SMP Negeri 2 Ende Selatan after using STAD type cooperative learning model. This research was a classroom action research (PTK) based on Kemmis & Mc Taggrat and utilized a qualitative approach. To collect the data, the researchers used (1) observation, (2) tests, (3) interviews, and (4) documentation. The data were analyzed with a descriptive qualitative method. The results of the study showed that (1) learning through picture – based STAD cooperative learning model increased the students’ active roles at grade VIII of SMP Negeri 2 Ende Selatan, (2) the use of picture – based STAD cooperative learning model also improved the students’ learning outcomes at grade VIII of SMP Negeri 2 Ende Selatan. This was showed from the mean score of the final test which increased from 54.40 to 77.95 in cycle II.